PRESENÇA DE MOLLICUTES E MYCOPLASMA BOVIS EM SWABS NASAIS DE BEZERROS E NO LEITE DE VACAS COM MASTITE CLÍNICA - Mayla Vasconcelos Adorno, Brunna; Salina, Anelise; Fernandes Joaquim, Sâmea; de Freitas Guimarães, Felipe; Churocof Lopes, Bruna; Menozzi, Benedito; langoni, Helio (Veterinária e Zootecnia, 2021)
Mycoplasma bovis is part of the bovine respiratory tract microbiota but is considered an opportunistic pathogen of extreme importance in respiratory diseases of calves. It causes to the herd several diseases such as mastitis, polyarthritis, pneumonia and endometritis. This pathogen is highly contagious and animals with mastitis are potential disseminators of infection to the herd since they release from 106 to 108 CFU per mL milk. Similarly, animals with pneumonia eliminate, through respiratory secretions, high microbial loads of the agent. The present study aimed to perform molecular detection of Mycoplasma bovis in 185 milk samples from cows with clinical mastitis, as well as in 50 nasal swab samples from healthy calves with or without signs of pneumonia and born from cows with mastitis, all belonging to four dairy farms in Paraná State, where cases of mastitis had beendiagnosed. DNA extraction from both secretions was carried out according to the thermolysis method. For polymerase chain reaction (PCR), generic primers were employed to amplify the Mollicutes DNA and positive samples were subjected to PCR with primersspecific for M. bovis. Positivity for M. bovis was 3.78% in milk samples, regardless of the farm, and 20% in nasal swabs.